A self-assembled DNA nanostructure for targeted and pH-triggered drug delivery to combat doxorubicin resistance. Issue 22 (16th May 2016) - Liu, Juan; Ma, Xiaowei; Lei, Chunni; Xue, Xiangdong; Wei, Tuo; Zhao, Jing; Li, Shuyi; Liang, Xing-Jie
Abstract : The self-assembled DNA nanostructure was able to specifically target cancer cells and release the drug at pH 5.0. Abstract : We developed a novel self-assembled DNA nanostructure for anticancer drug delivery. The resulting nanostructure was able to specifically target cancer cells and release the loaded drug at pH 5.0. More importantly, the drug-loaded DNA nanostructure effectively circumvented doxorubicin resistance of human lung adenocarcinoma epithelial cancer cells.